(untitled) (Annals of Medical Research, 2021)
Aim: To investigate the effects of using 5 mg/day tadalafil on inflammatory indicators including lymphocyte to monocyte ratio (LMR) and monocyte to high-density lipoprotein ratio (MHR) in patients with erectile dysfunction (ED).Material and Methods: This retrospective study included 62 subjects that 31 patients with ED and 31 healthy controls with a normal erectile function. The patients with ED were given a daily 5 mg dose of tadalafil over eight weeks. Baseline and post-treatment erectile function was evaluated using the International Index of Erectile Function (IIEF-5). Changes in IIEF-5 score and inflammatory indicators including LMR and MHR have compared both in ED patients and with controls.Results: The patients and the controls were statistically comparable with respect to age, Diabetes Mellitus, hypertension, coronary artery disease, CRP, testosterone, serum creatinine, lipid profile, LMR, and MHR. The mean IIEF-5 score was 22.97 vs 14.32 (p=0.001) in control and patients with ED, respectively. Having been used 5 mg of tadalafil per day over 8 weeks, an increase in IIEF-5 score (p=0.001) and a decrease in the number of monocytes (p=0.008) were detected in patients with ED. However, there was no statistically significant difference found in LMR and MHR before and after the treatment.Conclusion: According to the results of this study, no significant effect was found daily use of 5mg tadalafil on inflammatory indicators including LMR and MHR. The decrease in the number of monocytes that play a key role in inflammation may have been considered a response to treatment, however, randomized prospective studies are needed to evaluate the relationship among LMR, MHR and tadalafil treatment.